The Madrasah Excellent Class Learning ‎Innovation Management with Student-‎Centered Approach Base in Improving ‎Learning Achievement - Mawardi (State Islamic Institute of Madura, 2023)
This article aims to find and analyze the planning, implementation, and evaluation of learning innovations in excellent classes to improve learning achievement. This study applied a qualitative approach designed descriptively through a case study research type with a multicase research design. The research sites were conducted at MI International Sabilillah Sampang and MTs Negeri 3 Sumber Bungur Pamekasan. As a key instrument in the data collection, the researcher went directly to the field by applying previously planned techniques through participant observation, in-depth interviews, and documentation. Data analysis applied a case study with a multicase design which was analyzed through single data and data across cases. The study results show that the Excellent Class Learning Innovation lesson plan improves Learning Achievement at MI International Sabilillah Sampang and MTs Negeri 3 Sumber Bungur Pamekasan is built through input, excellent learning processes, and excellent output. Second, the implementation of excellent class learning innovations in improving learning achievement at MI International Sabilillah Sampang and MTs Negeri 3 Sumber Bungur Pamekasan, namely through a curriculum enriched with Olympiads, class management, standardized teachers, media management, and boarding schools. Third, evaluating learning outcomes using a test and non-test approach includes aspects of knowledge, attitudes, and skills with high competition standards so that student achievement and the reputation of the madrasah is increasing. In comparison, evaluating learning innovation programs uses the CIPP model by developing four components: context, input, process, and product.